Identity Tensions: Understanding a Previous Practitioner’s Decision to Pursue and Depart the Teaching Profession - Karalis Noel, Tiffany (Frontiers in Education, 2021)
Framed by symbolic interactionism, this study used narrative inquiry to share a teacher’s story about her decision to pursue and depart the teaching profession within four years of graduating from a traditional undergraduate preparation program in the Midwest United States. The participant, “Banjo,” participated in a qualitative analysis that consisted of four interviews conducted during the first year following her departure from the field. Findings revealed several conflicts surrounding Banjo’s sense of pre- and in-service teacher identity and teacher preparation experiences that ultimately influenced her decision to leave the teaching profession. Banjo’s story provides critical insights about how to prevent similar challenges among early-career practitioners and facilitate progressive change in preservice teacher education writ large.